COMMUNICATION COMPETENCY AND ABILITY TO ADAPT TO PERFORMANCE THROUGH WORKING SPIRIT - Purnama Pasande; Ezra Tari (JURNAL LUXNOS, 2020)
The writer examines the competence of communications in work that influenced the spirit of work. Communication used in work was still verbal and rarely used the available means. A leader's communication patterns with people he or she leads. The ability to communicate at work that can build up the spirit of work. Poor communication can affect employee spirit. The approach used in this research is a descriptive qualitative method in which to collect information and describe it in the study so that it sees one whole entity. Based on the thoughts carried out in this research, communication has a bearing on performance satisfaction, and this means that work satisfaction is influenced by communication. Another factor in influencing vigorous work is work facilities and infrastructure. The leadership factor is influential in delivering messages. A leader must care, participle, and be open to opinions.